ANALISIS PERBEDAAN FUNGSI PARU PADA PEMULUNG BERDASARKAN KADAR DEBU TOTAL DI TPS SAMPAH KOTA SEMARANG - Mia Eka Prinata; Nurjazuli Nurjazuli; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Scavenger is a community group that performs the activity of his work as parser trash in temporary landfill (TPS) and high-risk health disorders affected due to interact directly with the trash every day. Scavenger activity and means of transportation in the area temporary landfill produce high concentration of dust and cause a decrease in lung function capacity. This research aims to analyze the difference of lung function capacity (KVP and% VEP1%) on scavengers based on total dust concentration at TPS Semarang. This research is observational analytic study with cross-sectional approach. Data collection using the instrument is a questionnaire, spirometer and measurements of ambient dust concentration total. The research was conducted at three temporary landfill (TPS) in Semarang city, namely TPS Tembalang, Karangsaru, TPS and TPS Panggung Lor. Respondents taken in purposive sampling as many as 33 people. Total dust measurement results on the TPS Tembalang = 41,67 µ g/m3, TPS Karangsaru = 191.44 µ g/m3 and the TPS Panggung Lor = 254.32 µ g/m3. The results of the measurement of lung function capacity on scavenger using the spirometer as much 39.4% did not have a breakdown of pulmonary function (normal) Thirteen respondents and 60.6% (20 people) from 33 respondents underwent pulmonary function disturbances include mild restriction (39.4%), middle restriction (6.1%), heavy restriction (9.1%) and mixed (6.1%). The data were analyzed using one way anova test with significant level 95% (α = 0.05). The results of statistical tests the value of FVC (p = 0,135) and the value of FEV1 (p = 0,101) which means there is no difference in lung function capacity (FVC and FEV1% values) in the total dust concentration based on a scavenger at three temporary landfill (TPS) in the Semarang city. Conclusions on this research is the higher concentration of total dust in the polling stations, the higher the proportion of respondents who experienced lung function capacity impaired.